POLLINATION ECOLOGY OF OVIPAROUS SEMI-EVERGREEN MANGROVE TREE SPECIES, XYLOCARPUS GRANATUM KOEN AND X. MEKONGENSIS PIERRE. (MELIACEAE) AT CORINGA MANGROVE FOREST, ANDHRA PRADESH, INDIA - Solomon Raju, A. J. (Annali di Botanica, 2019)
Xylocarpus granatum and X. mekongensis are semi-evergreen tree species. Both species exhibit leaf fall, leaf flushing, flowering and fruiting sequentially. They are seasonal bloomers but also flower sporadically almost throughout the year. The flowers are functionally monoecious and exclusively pollinator-dependent. In cymes, the terminal flower is usually pistillate while the lateral ones are usually staminate. In X. mekongensis, solitary flowers are usually pistillate. In both, the pistillate and staminate flowers produce stamens with dehiscent anthers but ovary is functional only in the former while pollen is fertile only in the latter. Hawk moths are principal pollinators while butterflies and bees are supplementary pollinators in both plant species. Both species fruit through geitonogamy and xenogamy and fruit set in open-pollination is very low which could be attributable to unknown inherent regulatory mechanisms, delicate inflorescence and the production of a few pistillate flowers at plant level. The study suggests that there is an urgent need to protect the surviving trees and take measures to restore the populations of both the species